ANALYSIS OF CONSUMER DECISION FACTORS FOR MAXRIDE USAGE - Silvia Ekasari,; Revi Sesario,; Donny Dharmawan,; Musran Munizu,; Ramadhani Kirana Putra, (Journal of Innovation Research and Knowledge, 2025)
Maxride is an online transportation application that provides motorcycle taxi and taxi services based on bajaj. Maxride's passion lies in revolutionizing the landscape of three-wheeled transportation that is safe, comfortable, and accessible to everyone, while empowering local tricycle drivers. The purpose of this study is to describe the explanation of consumer decision factors for Maxride usage. The types of research used are qualitative and descriptive research. The data sources used in this study use secondary data. The results of the study indicate that consumer decisions to use Maxride Bajaj are the flexible seating capacity of MaxRide Bajaj and the agile cruising range of MaxRide Bajaj in overcoming traffic jams.